(untitled) (Medicine Today, 2017)
Diabetes mellitus is a silent killer which affects at any stage of life. Worldwide incidence of major malformation among the offspring of diabetic mothers ranges from 5-10%. Though 65-75% of birth defects are multifactorial, poor diabetic control in pregnancy predisposes congenital malformation. The aim of this retrospective study is to see the actual picture of congenital anomalies among the babies of uncontrolled diabetic mothers. Cases are taken from the hospital records of the patients who delivered congenitally abnormal babies & were admitted in SCABU of BIRDEM during the period of January, 2006 to December, 2010. After going through all records, patients were divided into DM/GDM/ND groups and different variables are studied. Among the patients (163), 57 (35%) were DM, 38 were (23.3%) GDM and 68 (41.7%) were ND. Major congenital anomalies were found 82.45% in DM and 71.05% in GDM and 83.82% in ND patients. Rests were minor anomalies. Among the anomalies maximum were congenital heart diseases, then CNS anomalies, then renalanomalies and then others. In this study congenital anomalies were found 1.4 times more in DM patients. Among DM and GDM patients maximum had uncontrolled blood sugar. Neonatal mortality was higher in DM and GDM groups. Both cardiac and CNS abnormalities were 1.2 times higher in diabetic groups. Renal anomalies were 2.8 times higher. Limb abnormalities were 7.15 times higher in diabetic groups. So it is concluded that pregnancy with uncontrolled diabetes increases the risk of birth defects, mainly CVS, CNS and Renal system related. Medicine Today 2017 Vol.29(1): 26-31